Historiografi Hadis di Eropa Pada Abad ke-19 dan ke-20 - Dandy Syauqy Muazar (Jurnal Ilmu Sosial dan Humaniora, 2025)
The history of hadith in 19th and 20th century Europe is inseparable from the role and influence of orientalists who brought hadith studies to the West. One of the first orientalists to criticise hadith was Gustav Weil followed by Aloys Sprenger. This paper attempts to look at the history of the development of hadith in Europe in 19th and 20th century as well as examples of some of the thoughts of orientalists who studied hadith in Europe at that time. This research is qualitative-descriptive with literature study method. The result of this study is that the history of hadith in Europe began in the 19th  century with the main figures Ignaz Goldziher and Joseph Schacht. They argued that there is no authentic hadith and that hadith is a product of the scholars of the second or third centuries of the hijriyah.